2020
DOI: 10.1021/acs.chemmater.9b03621
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Extent of Ligand Incorporation and the Effect on Properties of TiO2 Thin Films Grown by Atomic Layer Deposition Using an Alkoxide or an Alkylamide

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(76 citation statements)
references
References 68 publications
11
59
0
Order By: Relevance
“…they do not consist of particles) but, depending on the growth conditions, they include a variable concentration of pores and GBs. As shown in a previous work, 27 open porosity can be observed for as-grown samples but the pores are closed during the annealing. Such thermal treatment has been carried out for all films to avoid any direct deleterious contact between the silicon and the electrolyte.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…they do not consist of particles) but, depending on the growth conditions, they include a variable concentration of pores and GBs. As shown in a previous work, 27 open porosity can be observed for as-grown samples but the pores are closed during the annealing. Such thermal treatment has been carried out for all films to avoid any direct deleterious contact between the silicon and the electrolyte.…”
Section: Discussionsupporting
confidence: 74%
“…This can be easily correlated to morphology of the film that has been fully described in our previous work. 27 At low deposition temperature with TTIP, the TiO 2 film contains some tiny closed pores and, as seen on Fig. 2, the crystallite size is much smaller than with TDMAT.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Ti[(CH 3 ) 2 N] 4 or Tetrakis(dimethylamido)titanium(IV) (hereinafter TDMAT) and water. Despite the significant number of publication reporting on TiO 2 ALD from TDMAT and water [12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,31,33], there is no clear idea of all the possible chemical reactions on the surface during the growth process and also there is no unique behavior of growth curves (Growth Per Cycle) as a function of the growth temperature. Additionally, it was shown that the TiO 2 initial growth stages depend on substrate chemistry, as in the case of ZnO ALD [34,35,36,37], TiO 2 exhibit different types of growth depending on the surface [15,29].…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism involves precursor adsorption, proton transfer, and ligand elimination process, which has also been investigated in other metal oxide ALD processes such as TiO2 and SiO2. [36][37][38][39][40][41] In this study, we have studied the adsorption and ligand elimination process for two cerium precursors Tris(methylcyclopentadienyl)cerium(III) (Ce(MeCp)3) and Tetrakis(2,2,6,6tetramethyl-3,5-heptanedionato)cerium(IV) (Ce(TMHD)4) on TiO2 using density functional theory, while ALD experiments are carried out with Tris(i-propylcyclopentadienyl)cerium(III), Ce( i PrCp)3 and Ce(TMHD)4.…”
Section: Introductionmentioning
confidence: 99%